2022
DOI: 10.1111/jvh.13715
|View full text |Cite
|
Sign up to set email alerts
|

Posttreatment nonalcoholic fatty liver disease fibrosis scores for predicting liver‐related complications in patients with chronic hepatitis C receiving direct‐acting antiviral agents

Abstract: Patients with chronic hepatitis C (CHC) have a higher prevalence of hepatic steatosis and dyslipidaemia than healthy individuals. We analysed noninvasive fibrosis assessments, especially nonalcoholic fatty liver disease (NAFLD)‐related noninvasive fibrosis tests, for predicting liver‐related complications and hepatocellular carcinoma (HCC) occurrence in patients with CHC. This retrospective study enrolled 590 consecutive patients with CHC having a sustained virologic response (SVR) to direct‐acting antiviral a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Second, the current study had limitations related to missing follow-up data in the T-COACH and TACR databases, which led to the use of baseline information for outcome predictions. Generally, data from 12 or 24 weeks after antiviral therapy enable more accurate predictions [47]; however, the aforementioned limitations of the databases prevented us from analyzing such data. Third, although adopting a multicenter approach provides comprehensive patient data, it also introduces potential variability in normal values for laboratory tests across different hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the current study had limitations related to missing follow-up data in the T-COACH and TACR databases, which led to the use of baseline information for outcome predictions. Generally, data from 12 or 24 weeks after antiviral therapy enable more accurate predictions [47]; however, the aforementioned limitations of the databases prevented us from analyzing such data. Third, although adopting a multicenter approach provides comprehensive patient data, it also introduces potential variability in normal values for laboratory tests across different hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Noninvasive indices, such as FIB-4 score and the AST to platelet ratio index measured at the time of an SVR, were able to minimize the impact of HCV-induced hepatic necroinflammation [42]. Our previous findings indicate that noninvasive indices at PW12 had higher timedependent AUROC values than those at baseline [18]. Therefore, we used variables at PW12 to investigate the predictors of LREs and HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study demonstrated that noninvasive indices at PW12 had higher time-dependent AUROC values than did those at baseline for predicting LREs [18], and the presence of hepatic necroinflammation at baseline may affect the HSI. A time-dependent AUROC was used to assess the predictive performance of each type of metabolic dysfunction.…”
Section: Metabolic Dysfunction and Fib-4 Instead Of Hepatic Steatosis...mentioning
confidence: 91%
See 1 more Smart Citation
“…On other hand, in patients with CHC, cirrhosis was associated with atherosclerosis independently of cardiovascular risk factors (33) . Furthermore, abnormalities in lipid metabolism and subsequent hepatic steatosis are reported to be risk factors for the progression of liver fibrosis in these patients (34,35) .…”
Section: Introductionmentioning
confidence: 99%